Using electrical impedance to predict catheter-endocardial contact during RF cardiac ablation - Cao, Hong; Tungjitkusolmun, Supan; Choy, Young Bin; Tsai, Jang Zern; Vorperian, Vicken R.; Webster, John G. (My University, 2002)
During radio-frequency (RF) cardiac catheter ablation, there is little information to estimate the contact between the catheter tip electrode and endocardium because only the metal electrode shows up under fluoroscopy. We present a method that utilizes the electrical impedance between the catheter electrode and the dispersive electrode to predict the catheter tip electrode insertion depth into the endocardium. Since the resistivity of blood differs from the resistivity of the endocardium, the impedance increases as the catheter tip lodges deeper in the endocardium. In vitro measurements yielded the impedance-depth relations at 1, 10, 100, and 500 kHz. We predict the depth by spline curve interpolation using the obtained calibration curve. This impedance method gives reasonably accurate predicted depth. We also evaluated alternative methods, such as impedance difference and impedance ratio.
Keywords: Ablation; Biomedical electrodes; Biomedical measurements; Cardiovascular system; Conductivity measurement; Electrodes; Impedance measurement; Measurement